Re-estruturação produtiva em hospitais: estudo de caso em um hospital de Fortaleza-CE - Machado, Aldenis da Silva (2010)
The hospital, in its contemporary design, is a recent organization, complex and essential for life in society. Despite its peculiarities, its production methods and organization of work are based on models developed and applied in other sectors of the economy. Just as the model of Taylor and Ford spread by various sectors of the economy from the early twentieth century, becoming hegemonic, the technological and organizational innovations, initially promoted by the Japanese manufacturers have gained notoriety and recognition mainly from 1970s, being widely disseminated, including in hospitals. In Brazil, these innovations have emerged later, only after the early 1990s, with greater focus on organizational innovations. The aim of this study was to investigate how the intensity and productive restructuring impacted in the management process of a hospital. For this purpose, this study used the research literature, documentary and field research, conducted through a case study in a large hospital in Fortaleza-CE. Were used documentary analysis, semi-structured interview and a self-reported questionnaire as data collection instruments. The technique of data analysis used was content analysis. It was concluded that the most important technological innovations such as laparoscopic equipment, multi-parameter monitors, and ultrasound scanner, were introduced with more intensity in the intensive care unit - the ICU, the surgical center and diagnostic center, respectively. The main organizational innovations found were participatory management, committees of quality control, protocols for procedures, just in time and kaizen. The innovations were introduced following the logic of profitability and, more recently, more participatory. The repercussions were intensified exploitation of labor, bigger demand for qualified workers, increased demand, profitability and number of employees.